Simple Diagnostic Tests for Subungual Pigmentation - Shardul Poudyal; David J. Elpern (Hindawi Limited, 2009)
Subungual pigmentation can have benign and malignant etiologies. A common and important differential diagnosis is between subungual hematoma and subungual acrolentiginous melanoma. We have introduced Dr. Eckert Haneke's technique and our Hydrogen Peroxide modification for distinguishing these entities clinically. Dr. Haneke's technique uses the hemocult reaction to detect hematoma from the specimen, while our modification uses Hydrogen Peroxide to clear the hematoma and make the decision clinically. Both are minimally invasive techniques which can be performed without pain. Often these procedures spare the patient an unnecessary tissue biopsy with its morbidity and discomfort. Importantly, they reassure the patient that he or she has a benign disorder.